Pechakucha: Inovasi Pembelajaran untuk Mengembangkan Kemampuan Berbicara Calon Guru - Ni Wayan Ekayanti; Gusti Agung Paramitha Eka Putri; Dewa Ayu Puspawati (Universitas Sebelas Maret, 2018)
The teacher candidates must have public speaking skills in order to be able to deliver the subject matter to the students. But there are still many teacher candidates who are dare not to speak public. For that reason, it is necessary to do learning innovation which facilitates to develop speaking skill of teacher candidates. The purpose of this study was to analyze the response of teacher candidates when they implemented the PechaKucha technique at presentation. This research is a qualitative research by taking ethnography as its approach. Teacher candidates in 4 grade which amounted to 20 people is object of research. Data collection is done by observation, interview, discussion, and assessment task to obtain comprehensive data. Triangulation-based analysis data, which are fundamental in this ethnographic study. The results showed that 25% of teacher candidates stated that PechaKucha implementation was very useful in the presentation, 55% of teacher candidates stated useful and 20% stated normal, and no teacher candidates stated that there is no benefit in implementing PechaKucha presentation. So it can be concluded that the implementation of PechaKucha technique is very useful for teacher candidates to develop speaking skill.